Assessment of Postoperative Pain after Cesarean Section among Libyan Women Using a Standardized Questionnaire - Mahmud Abushhewa,; Omar Zaghlam,; Taha Abdulrahman,; Abdulati Salem,; Fauzia AbdusaLam,; Ashraf Naass,; Surur Alhidad,; Boshra Alnaier, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study analyzed postoperative pain experiences in 100 patients following cesarean sections (C/S), focusing on pain characteristics, medication efficacy, and functional impacts. Our findings revealed a high prevalence (87%) of moderate to severe pain, with significant correlations between pain intensity and factors such as age and number of C/S procedures. Younger patients (20–35 years) reported higher pain scores (p=0.023), and those with ≥3 C/S experienced more severe pain (p=0.008). Medication effectiveness varied by pain type, with stabbing pain responding better than aching pain (p=0.042). Severe pain was strongly associated with functional limitations, including breastfeeding difficulties (p=0.001), walking challenges (p<0.001), and sleep disturbances (p=0.003). The study underscores the need for enhanced multimodal analgesia strategies and personalized pain management to improve post-operative recovery outcomes for C/S patients.